Budget impact analysis of sarilumab for the treatment of rheumatoid arthritis in patients with an inadequate response to conventional synthetic DMARD or TNF inhibitor therapies [Corrigendum] - Ferrufino CP; Munakata J; Wei W; Proudfoot C; Kuznik A; Boklage SH; Chen C (Dove Medical Press, 2019)
Ferrufino CP, Munakata J, Wei W, et al. Clinicoecon Outcomes Res. 2018;10: 805—819. On page 810, Table 4, Drug costs column, Methotrexate, the Unit WAC was listed as $1 however it should have been $2.36. On page 817, Table S2, the monitoring costs for (A) csDMARD-IR and (B) TNF-IR were changed. Read the original article